Reading interests, reading habits and information needs of the urban poor in Constitution Hills, Quezon City a survey with the implication for providing library services for them - Viray, Jacoba de Guzman 1948- (1987)
Almost 100 precent of the respondents have reading materials in their homes consisting of newspapers, books and comics magazines. Reading on a once a week basis is high for the residents. The adults read more frequently and they have used library facilities more often than the youngsters.
Based on the findings, a library is recommended to be established in Constitution Hills containing materials that are relevant or are in consonance with the needs and interests of the urban poor residents.
Majority of the residents want a library established for them and supported by the government.
Sources of information of the respondents are the radio, newspapers and television. The people do not depend much on interpersonal relations as a source of information.
Subject preferences are varied among the two groups. The adults prefer materials on religion, family life, health and hygiene, earning a living and vocational skills. The youngsters read mostly textbooks, children's books and materials on religion. As subject preferences vary in age, they also vary according to educational attainment and occupations.
The respondents are a literate group. Sixty-seven percent have reached the elementary level, 30 percent have reached the secondary level while 3 percent have had collegiate education. Leisure time activities of the respondents include listening to the radio, reading and watching television.
This is a survey of the residents of Constitution Hills in Quezon City to determine their reading habits and interests, occupational patterns, literacy level, educational attainment, sources of information, subject preferences and their response to the idea of putting up a library in the locality. A 25-item questionnaire was the main data gathering instrument administered to 300 respondents consisting of 53 young males, 97 young females, 26 adult males and 124 adult females, chosen randomly. The dominant means of livelihood for the menfolk (35 per cent) is carpentry and laundering (10 per cent), for the womenfolk.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Books and reading -- Philippines -- Constitution Hills (Quezon City).; Information needs -- Philippines -- Constitution Hills (Quezon City).; Libraries and urban poor